Principal Accountability in the Governance of Islamic Education Programs: A Case Study at Madrasah Aliyah Wali Songo Tebo - Muttaqin; Sarmila; Sugeng Kurniawan; Talitha Dzakirah; M. Nuri Mu’allim; Baili (Jurnal Ilmu Pendidikan dan Sosial, 2022)
Public confidence in newly established madrasahs depends heavily on whether their principals can demonstrate measurable accountability when delivering Islamic education programs. Most existing studies, however, focus on long-standing institutions in urban centers, leaving rural and recently founded madrasahs in Sumatra largely unexamined. This article therefore investigates how the principal of Madrasah Aliyah Wali Songo Tebo a five-year-old institution serving 58 students in Jambi Province, Indonesia operationalizes accountability across the planning, implementation, and reporting phases of Islamic education programs, and identifies the determinants that shape such accountability. A qualitative single embedded case study design was employed between February and May 2025. Data were generated through 18 in-depth interviews with the principal, six teachers, and eleven purposively selected students, complemented by non-participant observation across 21 school days and document review of 14 program reports and budget vouchers. Data were analyzed using the interactive model of data condensation, display, and verification, with credibility secured through source and method triangulation, member checking, and an audit trail. Findings reveal that accountability is enacted through three structured programs hadroh, hitobah, and Islamic-holiday commemorations each documented with itemized budgets and post-event reports submitted to parents and the foundation board. Disciplinary accountability is enforced through a teacher attendance log, a 15-minute early-morning duty schedule, and a parent-approved IDR 10,000 truancy fine. Four determinants emerge: leadership competence, personal integrity, supervision-and-regulation systems, and resource sufficiency. Although funding and facilities meet ministerial standards, teacher shortages compel several teachers to handle up to three subjects, weakening pedagogical effectiveness. The study concludes that accountability functions as a multidimensional managerial mechanism rather than a purely administrative obligation, and that human-resource sufficiency is its most fragile pillar in newly established rural madrasahs.